Konsepsi Penyelamatan Dana Desa Dari Perbuatan Korupsi - Bunga, Marten; Aswari, Aan; Djanggih, Hardianto (Halu Oleo Law Review, 2018)
This paper aims to analyze the management of village funds from corruption. The problem focuses on how the concept of saving village funds from corruption? This research is in the form of normative legal research with approach of legal norm and legal principles. The result of the research shows that the concept of fund grant from villages from corruption bundles, namely, First, MoU with community with the aim of committing to build village together with village fund monitoring team; Second, establishing an independent team of supervisors to oversee the running of village fund management processes; third, ready to be sworn the village apparatus in the oath by using the scriptures of each religion; four strict sanctions with a view to providing perpetrators of village funds.